Enhanced visible-light photocatalytic activity of multi-elements-doped ZrO2 for degradation of indigo carmine - Agorku, E.S.; Kuvarega, A.T.; Mamba, B.B.; Pandey, A.C.; Mishra, A.K. (Journal of rare earths, 2015)
In this study, C,N,S-doped ZrO2 and a series of Eu doped C,N,S-ZrO2 photocatalysts were synthesized by a coprecipitation method using thiourea as the source of C, N and S and Eu（NO3）·6H2O as source of Eu. The materials were characterized by X-ray dif-fraction （XRD）, Raman spectroscopy, Fourier transform infrared spectroscopy （FTIR）, UV-visible diffuse reflectance spectroscopy, scanning electron microscopy （SEM）/energy dispersive X-ray spectroscopy （EDX）, and transmission electron microscopy （TEM）. Indigo carmine （IC） was chosen as a model for organic pollutants and used to evaluate the photocatalytic performance of the photo-catalysts under simulated solar light. Commercial ZrO2 was used as a reference material. XRD and Raman results indicated the for-mation of both tetragonal and monoclinic phase ZrO2 with particle size ranging from 8–30 nm. Multi-element doping had a great in-fluence on the optical responses manifested as red shift in the absorption edge. The highest photocatalytic activity towards IC was observed for the Eu,C,N,S-doped ZrO2 （0.6 mol.%Eu） sample （k=1.09×10–2 min–1）. The commercial ZrO2 showed the lowest photo-degradation activity （k=5.83×10–4 min–1）. The results showed that the control of Eu doping in the C,N,S-ZrO2 was very important in reducing electron-hole recombination. The synergistic effect of Eu, C, N, and S in the ZrO2 matrix led to enhanced utilization of simulated solar energy for the degradation of IC through narrowing of bandgaps.